ChemInform Abstract: Rhodium‐Catalyzed Enantioselective Hydrogenation of β‐Acylamino Nitroolefins: A New Approach to Chiral β‐Amino Nitroalkanes. Issue 12 (25th March 2014) - Zhou, Ming; Dong, Dejun; Zhu, Baolin; Geng, Huiling; Wang, Yan; Zhang, Xumu
Abstract By using TangPhos as chiral ligand a series of β‐amino nitroalkanes are obtained in high yields and with good enantioselectivities.